Uso de leveduras como ferramenta enológica na fermentação de vinhos Gewurztraminer - Santos, Patrícia de Souza dos (2018)
The present work had the objective of analyzing and evaluating the behavior of yeasts in the fermentation of must of the variety Gewurztraminer, from the Region of Campanha, municipality of Santana do Livramento. The fermentation process was carried out at the Experimental Winery of the Federal University of Pampa, Campus Dom Pedrito. The experiment consisted of five treatments: T1: Saccharomyces cerevisiae, T2: Saccharomyces cerevisiae var. cerevisiae, T3: Saccharomyces cerevisiae var. bayanus, T4: Toruslapora delbrueckii and T5 Metschinikowia pulcherrima. During two weeks the dependent variables related to fermentation kinetic characteristics were evaluated. The first treatment to finish the process of alcoholic fermentation was the T3 to the tenth day. The T4 treatment was the last treatment to complete the process on the fourteenth day. Regarding alcohol production, the treatment that presented the best results was T3, with a 12.7% alcohol content. On the other hand, the treatment with lower performance in the transformation of sugar into alcohol was T4, with 11.9% of alcoholic strength. Yeasts of the genus Saccharomyces present the best performances, with fast fermentations, with good conversion of sugar to alcohol. Saccharomyces yeasts have a complete fermentation capacity and low production of volatile acidity, and can be an alternative in the fermentation of wines from Region Gaucho Campaign.